Modernity between Wagner and Nietzsche - Polka, Brayton (Lanham : Lexington Books, 2015)
Modernity between Wagner and Nietzsche argues that the operas and writings of Wagner contradict the values that are fundamental to modernity. Analyzing Wagner's works in contrast to the philosophical thought of Nietzsche, Brayton Polka examines how Wagner breaks with Nietzsche and their common influencer, Schopenhauer.
Title Page; Acknowledgments; Introduction; Wagner's Ring; Tristan und Isolde; Parsifal; Postlude Recapitulated as Prelude in Nietzsche; Conclusion; Bibliography; Index; About the Author.
Print version record.
Keywords: Christian philosophy; Nietzsche, Friedrich Wilhelm, 1844-1900.; Philosophy and religion; Philosophy, Modern -- 19th century; Wagner, Richard, 1813-1883.; Wagner, Richard, -- 1813-1883.; Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Philosophy, Modern -- 19th century; Christian philosophy; Philosophy and religion; PHILOSOPHY / History & Surveys / Modern; Electronic books